Discerning Cultural Identification From a Thinly Sliced Behavioral Sample - Hamamura, Takeshi; Li, L. (Sage Publications, Inc., 2012)
This research examined whether individual differences in cultural identification can be discerned at zero acquaintance. This issue was examined in Hong Kong, where the idiosyncrasy of cultural identification is a salient social-psychological issue. The participants were able to perceive accurately the targets’ identification with Western culture from a video clip and from a still image. Findings also indicated that a stereotype of Western cultural identity (i.e., extraversion and particular hairstyle) facilitated these perceptions. Specifically, (a) the participants with a stronger stereotype were more accurate in perceiving Western cultural identification, (b) the targets who were experimentally manipulated to appear extraverted were rated as more strongly identifying with Western culture, and (c) the participants relatively unfamiliar with these stereotypes did not correctly perceive Western cultural identification. Implications of these findings on research on multiculturalism are also discussed.